Artificial Intelligence in ESP Education: Student Insights and Future Directions - Ramdha, Triana; Kurnia, Rita; Agustiani, Aulia; Mirfaturiqa (Sekolah Tinggi Teknologi Pekanbaru, 2025)
This article focuses on the use of artificial intelligence in the teaching of ESP with emphasis on the students’ perception. It emphasizes on the increasing importance of English language in the world and how the incorporation of Artificial Intelligence in education makes learning more effective. This research adopts a quantitative research approach that involved the use of questionnaires distributed to engineering students and English lecturers in a university in Indonesia. The results suggest that young students have positive attitude towards integration of AI in their learning while the older students have either mixed or negative attitude. The study also shows that there are stark variations in how useful AI is considered across the different engineering disciplines. This study implies that although the use of AI in ESP teaching and learning enhances students’ learning engagement and achievement, AI has to be implemented in a way that considers students’ demographic characteristics and learning requirements. The study calls for more research to improve the use of AI in learning environments and to help learners meet market requirements.